Sectarian Religion and Political Tolerance in the United States. (19th September 2018) - Schwadel, Philip; Garneau, Christopher R H
Abstract: Many Americans oppose granting civil rights to stigmatized outgroups. This lack of political tolerance is strongly associated with sectarian Christianity. We argue that the association between sectarian religious affiliation and political tolerance has diminished but that the effects of sectarian belief on tolerance remain prevalent. Using more than three decades of repeated cross-sectional survey data and hierarchical age-period-cohort models, we find precipitous across-period and across-cohort convergence in political tolerance between affiliates of evangelical Protestant denominations and other Americans. The effects of biblical literalism on political tolerance also decline, but remain relatively robust. Additional models show how both religious affiliation and views of the Bible influence tolerance of specific outgroups in the contemporary context. We conclude by discussing the implications of the results for both social scientific research and the vibrancy of American democracy.